Phenomenology of anxiety - Micali, Stefano (Phaenomenologica, 2022)
Dedication -- Chapter. 1 -- Introduction -- Chapter. 2 -- Anxiety Between Terror and Fear -- Chapter. 3 -- Anxiety between negative connotation and positive teleology: Sartre, Kierkegaard and Heidegger -- Chapter. 4 -- Anxiety, Desire and Imagination -- Chapter. 5 -- Anxiety: A Phenomenological Investigation in V Acts.